Invasive cervical resorption: An endodontic challenge managed by intentional replantation - Madhu Ahra; Tasneem Abuwala; Girish Parmar (Wolters Kluwer Medknow Publications, 2019)
Invasive cervical resorption (ICR) is an aggressive form of tooth resorption that is not well understood. Accurate diagnosis and early management are prerequisites for long-term retention of the tooth. Treatment procedure includes eliminating the resorptive tissue followed by restoring the defect with a suitable biocompatible material. This case report is on successful management of an ICR lesion; inaccessible to the conventional procedure; by root canal treatment and intentional replantation (IR) of the tooth for complete debridement and sealing of resorptive site with biodentine. At 18-month recall, the tooth was clinically sound with no radiographic evidence of inflammatory or replacement root resorption. Thus, IR should be considered as a viable treatment option.